The Effects of Problem Posing Learning Model on Students’ Learning Achievement and Motivation - Agatha Puri Christidamayani; Yosep Dwi Kristanto (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2020)
Posing high-quality problems is a critical skill to be possessed by students in learning mathematics. However, it is still limited in literature in answering whether problem posing learning model effective in improving students’ learning achievement and motivation. Therefore, the present study aims to investigate the effect of problem posing learning model in the topics of cube and cuboid on students’ learning achievement and motivation. This study employs quasi experimental design with 20 students in experimental group and 24 students in control group. The study found that the problem posing learning model has insignificant effect on the students’ learning achievement but has a positive and significant effect of the learning model on the students’ learning motivation. Further analysis showed that the learning model also has a significant and positive effect on every aspect of students learning motivation, namely students’ interests, enthusiasm, diligence, collaboration, and self-control.